Health Education About Diet for Chronic Kidney Disease (CKD) Patients to Handle Knowledge Deficits in Hospital Patients (Nursing Case Study at RSUD Sleman) - Catur Budi Susilo; Hani Setyoningsih; Abdul Majid; Budi Ermawan; Dawam Jamil (PT FORMOSA CENDEKIA GLOBAL, 2023)
The kidney is a functional metabolic organ for substances in the body, including glomerular filtration, reabsorption, secretion, acidification of urine, production and metabolism of hormones. One of the treatments for kidney failure is hemodialysis. Apart from hemodialysis, health education on a low- salt diet and fluid restriction in patients with chronic kidney failure is also very necessary to maintain patient survival as part of their treatment. To find out the application of health education on Diet Chronic Kidney Disease (CKD) in CKD patients in overcoming the problem of knowledge deficit nursing. Using the case study method by applying the nursing process approach through the implementation of the CKD Diet health education. The subjects used were two patients with the same problem. The study obtained data that the two respondents did not know the CKD Diet correctly and obtained priority nursing diagnoses with knowledge deficits associated with less exposure to information. After carrying out nursing actions for three days, the results of the evaluation of the two patients experienced an increase in knowledge power marked by when asked the client could answer and explain according to what was previously described. After the two respondents were given the CKD Diet health education action, the knowledge deficit nursing problem was resolved, marked by the client already knowing about the disease diet and already knowing what to do next.